Structure activity relationship studies of new ethylene antagonists - Musa, Muftah Miloud A. (Curtin University, 2016)
Ethylene antagonists provide one of the most effective methods to reduce postharvest losses of horticulture produce. The understanding of the mode of action of 1-methylcyclopropene led to the discovery of a new class of ethylene antagonist. Cycloproparenes, benzocyclopropene and 1H-naphtho[b]cyclopropene were prepared and showed excellent inhibition of the effect of ethylene on some fruits and waxflowers.